Psychometrics as a Tool to Improve Screening and Access to Credit - Arráiz, Irani; Bruhn, Miriam; Stucchi, Rodolfo (World Bank, Washington, DC, 2015)
This paper studies the use of psychometric tests, which were designed by the Entrepreneurial Finance Lab as a tool to screen out high credit risk and potentially increase access to credit for small business owners in Peru. The analysis uses administrative data covering the period from June 2011 to April 2014 to compare debt accrual and repayment behavior patterns across entrepreneurs who were offered a loan based on the traditional credit-scoring method versus the Entrepreneurial Finance Lab tool. The paper finds that the psychometric test can lower the risk of the loan portfolio when used as a secondary screening mechanism for already banked entrepreneurs—that is, those with a credit history. For unbanked entrepreneurs—those without a credit history—using the Entrepreneurial Finance Lab tool can increase access to credit without increasing portfolio risk.